How Can We Attract and Retain Quality School Principals: What Do Principals Say? - M. Scott Norton (Educational Considerations, 2004)
Attracting quality personnel for leadership roles as school principals and then retaining their services have become national concerns. Studies reveal that turnover in the principalship at both elementary and secondary schools reached the 50% level during the 1990s, with predictions that such losses are likely to increase during the current decade.